Strength of pelvic floor in men: reliability intra examiners - Patricia Zaidan; Fabio Dutra Pereira; Elirez Bezerra da Silva (Editora Champagnat, 2018)
Abstract Introduction: The obtaining of urinary continence is due to the strength of the pelvic floor muscles (MAPs) at the moment of muscle contraction, when there are sudden increases in intra-abdominal pressure, which increases urethral closure pressure and decreases the possibility of urinary loss. Objective: To verify the reliability, type: stability, intra-examiner, of the measure of the strength of MAPs held with Peritron. Methods: Test and retest study to assess the intra-rater reliability of Peritron to measure the strength of MAPs. The sample consisted of 36 male patients, mean age 65.3 ± 7.2 years, all with urinary incontinence (UI) after radical prostatectomy. The physical therapist conducted a training for familiarization with the procedures of MAPs strength assessment with Peritron for two weeks. The strength of MAPs was measured by a perineometer of the Peritron brand (PFX 9300®, Cardio-Design Pty. Ltd, Baulkham Hills, Australia, 2153). Results: The intraclass correlation coefficient (ICC) was equal to 0.99; P = 0.0001. The typical measurement error (ETM) was equal to 3.1 cmH2O and ETM% of 4. Conclusion: Peritron showed high reliability for measuring the strength of MAPs in men, both for clinical practice and for the production of scientific knowledge. It should be noted that such measures were carried out in stability, so it is suggested that in internal consistency reliability is equivalent.